Personality factors and style of coping with stress in women and men - Antonów, Karolina; Zdziarski, Krzysztof (Journal of Education, Health and Sport, 2022)
This article presents personality factors juxtaposed with coping styles among men and women aged 18 to 71 years. The first section describes the concept of personality, its components, and the definition of stress and coping styles. Personality traits were examined using the NEO-FFI Personality Inventory and coping styles were examined using the Coping with Stress Questionnaire (CISS). The study was conducted in a sample of 175 men and women, and data were collected using online methods. There was a positive correlation between task-focused style and extraversion, openness to experience, agreeableness, and conscientiousness. In contrast, between the emotion-focused style a very strong positive correlation was shown only with neuroticism. There are low or statistically insignificant correlations between avoidance-focused style and personality factors.